2011
DOI: 10.1021/bi201286p
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Analysis of Binding of WW Domains of the YAP2 Transcriptional Regulator to PPXY Motifs within WBP1 and WBP2 Adaptors

Abstract: YAP2 transcriptional regulator mediates a plethora of cellular functions, including the newly discovered Hippo tumor suppressor pathway, by virtue of its ability to recognize WBP1 and WBP2 signaling adaptors among a wide variety of other ligands. Herein, using isothermal titration calorimery (ITC) and circular dichroism (CD) in combination with molecular modeling (MM) and molecular dynamics (MD), we provide evidence that the WW1 and WW2 domains of YAP2 recognize various PPXY motifs within WBP1 and WBP2 in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 49 publications
3
47
0
Order By: Relevance
“…The interaction with Smad2/3 entails the TAZ coiled-coil domain (207). The WW domains are essential for YAP-induced cell proliferation (261) and mediate binding of YAP/TAZ to PPxY motif-containing transcription factors such as RUNX, p73, and the cytoplasmic domain of ERBB4 or with the transcriptional cofactor WBP2 (28,40,104,140,164,197,214).…”
Section: Nuclear Yap/taz Complexesmentioning
confidence: 99%
“…The interaction with Smad2/3 entails the TAZ coiled-coil domain (207). The WW domains are essential for YAP-induced cell proliferation (261) and mediate binding of YAP/TAZ to PPxY motif-containing transcription factors such as RUNX, p73, and the cytoplasmic domain of ERBB4 or with the transcriptional cofactor WBP2 (28,40,104,140,164,197,214).…”
Section: Nuclear Yap/taz Complexesmentioning
confidence: 99%
“…In binding with cyclic form of pep63, the exchanging regime of two of these residues, Y26 and H30, change from fast to slow, indicating the formation of a less shaky complex induced by a more stable conformation of the peptide. Similarly, as described for Yap2-WBP2 complex, 46 in the WW2-pep63 OX complex, the formation of a hydrogen bond between Hη phenolic hydrogen of Y within the PPxY motif and H-HSQC spectra, the lines underline some of the major differences observable.…”
Section: Discussionmentioning
confidence: 58%
“…The above data are in agreement with recent thermodynamic studies that suggested strongly that non-consensus residues within and flanking the PPxY peptides are important for stabilizing the peptide conformation, and that peptides with distinct conformations are optimally suited for binding to WW domains. 46 The balance among rigidity and flexibility of both WW domains and protein targets might also be an in vivo critical factor in this molecular recognition mechanism. Accordingly, the WW-ligand interactions are usually studied in vitro using short, proline-rich peptides, and the relatively low affinities observed (in 10 to 100 μM) are generally characteristic of several similar data strongly suggest that the interaction of the domain with the cyclic form of the peptide results in a more stable complex with a longer lifetime than that resulting from the interaction with the linear form of pep63.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations